Penerapan Budaya Kaizen untuk Meningkatkan Motivasi Berwirausaha Dikalangan Mahasiswa - Darham Wahid; Yudhi Novriansyah; Supriyati Supriyati; Herawati Herawati; Khairun A Roni (Kesejahteraan Bersama : Jurnal Pengabdian dan Keberlanjutan Masyarakat, 2025)
In order to enhance the entrepreneurial spirit among the younger generation, especially among students, the Faculty of Economics teaching staff, supported by the Research and Community Service Institute (LPPM) of Muara Bungo University, conducted Community Service activities with the theme "Application of Kaizen Culture to Enhance the Entrepreneurial Spirit Among Students." This community service activity was conducted in the Auditorium of Muara Bungo University. The method used is a Seminar with a participatory learning approach. The results of the Entrepreneurship Seminar are expected to enhance the spirit and entrepreneurial mindset of students by being to apply the Kaizen Culture philosophy. Where students can become entrepreneurs themselves, which, if pursued diligently, can become a promising alternative profession that can serve as a primary source of income in the future.